Rhetoric of Hadith: Descriptive and Analytical study - Azraq, Hamda Ahmed Othman (Journal of Humanities & Social Sciences, 2020)
The Prophetic Hadith is a crucial and important source for grammatical and rhetorical studies in language. It was always considered a valuable source of guidance and remains to be one of the major reference points for scholars in language because the prophet May peace and blessings be upon him was one of the most linguistically talented individuals in his clarity, and grammatical use. Furthermore، he was experienced in understanding of pragmatic and syntax use of the Arabic language. All these qualities and the authenticity of the Hadiths make is second most important text after the holy QuranThis study showed the Prophet’s (peace be upon him) rhetoric and linguistic knowledge were among the most prominent signs of his magnificence and grace. Also, It confirms his undeniable prophet- hood as he, (peace be upon him), possessed mastery of the spoken language, unattainable wisdom, truthful speech, straight path, and infinite miracle. Allah the Almighty said: “Nor does he speak out of desire. It is naught but revelation that is revealed.” And Allah the Almighty also said: “The faithful spirit has defended with it. Upon your heart that you may be of the warners. In Plain Arabic Language.”This study addressed the linguistic and terminological meaning of rhetoric and explained the reasons for the eloquence of the Hadith and the beauty if use of language without and additions or unnecessary use of words, as well as the superior ability to inspire visual responses via the use of similarity, repetition, interrogation, metaphor, dialogue, suspense and all the skills performed by the Prophet's Hadith according to the nature of the situation, and the context all whilst taking into account the case the listeners through the choice of words and phrases appropriate to their minds to elicit clear understanding and persuasion. All these points were supported by evidence from the Hadith to confirm and strengthen this study.
Keywords: eloquence; hadith of the Prophet; Arabic language